2010
DOI: 10.1093/icesjms/fsq147
|View full text |Cite
|
Sign up to set email alerts
|

Metazoan parasites of swordfish, Xiphias gladius (Pisces: Xiphiidae) from the Atlantic Ocean: implications for host stock identification

Abstract: Garcia, A., Mattiucci, S., Damiano, S., Santos, M. N., and Nascetti, G. 2011. Metazoan parasites of swordfish, Xiphias gladius (Pisces: Xiphiidae) from the Atlantic Ocean: implications for host stock identification. – ICES Journal of Marine Science, 68: 175–182. The metazoan parasite fauna composition of the swordfish Xiphias gladius is reported from 157 fish caught in four areas of the Atlantic Ocean: northwest (NW), central north (CN), eastern tropical (ET), and central south (CS). Samples were collected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 42 publications
8
30
0
Order By: Relevance
“…It is, therefore, surprising to note that these parasites can withstand the muscular activity in the intestine of the host and are not voided along with the faeces. F. plicatus is the specialist parasite for X. gladius (Garcia et al 2010) and as documented in this study, has shown high prevalence and intensity in the swordfish from the Atlantic Ocean (Hogans and Hurley 1986;Garcia et al 2010). Similar to the findings in the present study, Hogans and Hurley (1986) had documented the variations in the morphology of scoleces of F. plicatus collected from the northwest Atlantic Ocean.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…It is, therefore, surprising to note that these parasites can withstand the muscular activity in the intestine of the host and are not voided along with the faeces. F. plicatus is the specialist parasite for X. gladius (Garcia et al 2010) and as documented in this study, has shown high prevalence and intensity in the swordfish from the Atlantic Ocean (Hogans and Hurley 1986;Garcia et al 2010). Similar to the findings in the present study, Hogans and Hurley (1986) had documented the variations in the morphology of scoleces of F. plicatus collected from the northwest Atlantic Ocean.…”
Section: Discussionsupporting
confidence: 56%
“…The swordfish (Xiphias gladius Linnaeus, 1758) and long snouted lancetfish (Alepisaurus ferox Lowe, 1833) are two important large pelagic predators inhabiting the tropical, temperate, and sometimes cold waters of the world oceans (Froese and Pauly 2011). Parasite fauna of these fishes is fairly well documented in the Atlantic and the Pacific Oceans (Monticelli 1889 ;Nigrelli 1938;Yamaguti 1959;Gibson and Bray 1977;Hogans et al 1983;Scholz et al 1998;Castro-Pampillon et al 2002;Garcia et al 2010). However, the metazoan parasites of these predators in the Indian Ocean are poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…type II HD (Sequeira et al 2010) and Anisakis sp. in Xiphias gladius from Cape Verde (Garcia et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Such use of Ansakis spp. as biological indicator for host fish stocks identification have been used particularly for Atlantic horse mackerel [21,15,16], Jack mackerel (Trachurus symmetricus murphyi) [102], European hake (Merluccius merluccius) [14,15], swordfish (Xiphias gladius) [15,20], and herring (Clupea harengus) [18]. Other metazoan parasites, apart from Anisakis, have also been reported as possible use to distinguish fish stocks of rough scad (Trachurus lathami) [19] and herring [18].…”
Section: Biological Indicators For Environmental Pollutions (General mentioning
confidence: 99%